Higher Maternal Protectiveness Is Associated with Higher Odds of Child Overweight and Obesity: A Longitudinal Australian Study - Hancock, Kirsten J. (Public Library of Science, 2014)
In recent years there has been an increasing interest in overprotective parenting and the potential role it plays in child development. While some have argued that a trend towards increased parental fear and reduced opportunity for independent mobility may be linked to increasing rates of child overweight and obesity, there is limited empirical information available to support this claim. Using data from the Longitudinal Study of Australian Children, this study aimed to examine the longitudinal relationships between maternal protectiveness and child overweight and obesity. A cohort of 4–5 year old children was followed up at 6–7, 8–9 and 10–11 years of age (n  =  2596). Measures included a protective parenting scale administered when children were 6–7 and 8–9 years of age, child body mass index (BMI), family characteristics including household income, neighbourhood disadvantage, child's position amongst siblings, and maternal BMI, education, employment, mental health and age at first birth. International Obesity Taskforce age- and sex-specific BMI cut points were used to determine if children were in the normal, overweight or obese BMI range. There was no association between maternal protectiveness and the odds of children being overweight or obese at age 4–5, 6–7 or 8–9 years. However at age 10–11 years, a 1 standard deviation increase in maternal protectiveness was associated with a 13% increase in the odds of children being overweight or obese. The results provide evidence of a relationship between maternal protectiveness and child overweight and obesity, however further research is required to understand the mechanism(s) that links the two concepts.